Extensometria aplicada à determinação das deformações resultantes das tensões de secagem em madeira de Corymbia citriodora - Sánchez, José Yony Cricel Sima (2017)
Log sawing and wood drying must be performed according to appropriate techniques to minimize the appearance of defects. However, the quality of the raw material must also be taken into account in order to obtain lumber of good quality at the end of processing. In the removal of water from the wood, moisture gradients originate between the inner and outer layers of the pieces, which generate stresses, favoring the appearance of warping and cracks. The conditioning step at the end of the drying is an alternative to relieve drying stresses. The most common method for evaluating them is the fork test. However, this method is destructive, time-consuming and does not quantify the defect. To contribute to the best evaluation of the drying stresses it was assumed that they could be measured with a strain gauge used to measure deformations in trees, resulting from growth stresses. The objective of this study was to quantitatively evaluate the deformations resulting from the drying stresses (DTS) of the tension and the opposite wood formed in inclined trees and the normal wood, formed in upright trees, using a strain gauge. Six trees of Corymbia citriodora were cut, at the age of 60, three upright and three inclined, which were later sawn and dried up to 12% in a conventional kiln drying. The drying program employed was based on initial and final temperatures of 40 and 65°C, respectively, and drying potential equal to 2.1. The DTS were measured post-drying and post-conditioning in steam, on hot and cold lumbers. The digital strain gauge measured the deformation by the spacing between two pins fixed longitudinally on the surface of the boards, after the execution of a bore 20 mm in diameter. After drying, the hot and cold boards presented, on average, DTS equivalent to 26 and 15 um, respectively. These values were significantly different, demonstrating the relief of DTS after cooling of the boards. Timber from upright trees showed averages of DTS higher than those from inclined trees. In the tension wood, the DTS averages (17 um) were lower than those found in the opposite wood (21 um). The strain gauge was reliable to quantitatively measure the DTS, having the potential to be employed in the quality control of the drying.